REM sleep and catecholamine excretion: a study in elite athletes - Netzer, N. C.; Kristo, D.; Steinle, H.; Lehmann, M.; Strohl, K. P. (European Journal of Applied Physiology, 2001)
We investigated the potential influence of catecholamines on sleep architecture in endurance-trained athletes. The hypothesis was that endogenous levels of aminergic neurotransmitters influence sleep architecture. Thirteen well-trained male street cyclists (all members of the German national amateur team, mean age 23.9 years, mean body mass index 21.9 kg/m2) completed the protocol. Each subject was studied during training after a race competition (C) and later in a recovery/rest period (R) with no training and no competition. Polysomnography (PSG) was performed for one night (C) and for a second night some weeks later (R). Urinary levels of catecholamines collected during the preceding day and over the night of PSG were used as an index of excretion rate of circulating adrenergic agonists. Nighttime and daytime excretion of epinephrine and norepinephrine was significantly elevated after exercise (C vs R; P<0.01). Rapid-eye-movement sleep (REM) onset latency was significantly increased (P=0.03) and REM was significantly decreased in the first half of the night in the training compared to the resting condition (C vs R, P=0.05). REM latency was correlated with increased epinephrine excretion on the day of exercise (C, r=0.63, P=0.02). The temporal appearance of REM during the night appears to be affected in part by the intense exercise associated with race competition, and urinary catecholamines are markers that are correlated with this alteration in REM appearance.